2018
DOI: 10.7249/rr2685
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Methods to Estimate the Effect of State Laws on Firearm Deaths: A Simulation Study

Abstract: This document and trademark(s) contained herein are protected by law. This representation of RAND intellectual property is provided for noncommercial use only. Unauthorized posting of this publication online is prohibited. Permission is given to duplicate this document for personal use only, as long as it is unaltered and complete. Permission is required from RAND to reproduce, or reuse in another form, any of its research documents for commercial use. For information on reprint and linking permissions, please… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 49 publications
2
52
0
Order By: Relevance
“…Findings from our simulations on opioid-related mortality are highly similar to findings for total firearm deaths considered in Schell, Griffin, and Morral (2019). The models considered here are virtually identical to the models considered in the Schell, Griffin, and Morral (2019) study, though we expand the simulation scenarios to consider performance across a wider range of assumed effect sizes of the law (5% to 25% versus 3% in Schell, Griffin, and Morral (2019)). In their case, one model proved optimal across all performance metrics considered: the negative binomial AR model, whereas we found in favor of two set of models of which the negative binomial AR model is one.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Findings from our simulations on opioid-related mortality are highly similar to findings for total firearm deaths considered in Schell, Griffin, and Morral (2019). The models considered here are virtually identical to the models considered in the Schell, Griffin, and Morral (2019) study, though we expand the simulation scenarios to consider performance across a wider range of assumed effect sizes of the law (5% to 25% versus 3% in Schell, Griffin, and Morral (2019)). In their case, one model proved optimal across all performance metrics considered: the negative binomial AR model, whereas we found in favor of two set of models of which the negative binomial AR model is one.…”
Section: Discussionsupporting
confidence: 63%
“…The simulation design builds directly from prior work that compared statistical methods for evaluating the impact of state laws on firearms deaths (Schell, Griffin, and Morral 2019). For each simulation iteration, we selected a random subset of k states to be the policy/treated group (i.e., it = 1 at some point in the study period), with remaining states serving as the comparison group (i.e., it = 0 for the entire study period).…”
Section: Simulation Data Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although models commonly used in policy analysis often include both state and time fixed effects, emerging research on the effect of state laws on firearms deaths indicates the best model may depend on how the exposure is operationalized and whether autoregressive terms are used . Among nonautoregressive models, Schell et al found that using time fixed effects with adjustment to the standard error via GEE was competitive with the best performing model which uses time fixed effects, change levels coding of the law exposure variable, lags of the outcome, and no adjustment to the standard error.…”
Section: Methodsmentioning
confidence: 99%
“…Another improvement is state-specific trend variables. Perhaps the most important controls are lagged dependent variables (Schell, Griffin, & Morral, 2018;Spelman, 2016). They control for missing variables that affect the dependent variable through its lag.…”
mentioning
confidence: 99%